CLINICAL AND NEUROPHYSIOLOGIC VERIFICATION OF AGERELATED DIFFERENCES IN EPILEPSY IN CHILDREN AND ADOLESCENTS - Djurabekova Aziza Tokhirovna; Marjona Furkatovna Umarova; Kseniya Vladimirovna Shmyrina (Scholar Express Journals, 2024)
Epilepsy of childhood and adolescence, is a problem of interdisciplinary approach, many specialists. The polymorphism of transformation in the body of the young generation, requires a clearer approach not only to the diagnosis of the disease, but also to the optimization of treatment, taking into account the interaction of drugs with each other, their influence on hormonal status, fertility indicators and other side effects. Globally, there are more than 10 million children under 15 years of age who are registered with active epilepsy, which is approximately 25% of the total population affected by this pathology (1, 5). Interestingly, the incidence shows declines over time, so up to 50 per 100000 after 9 years of life. In addition, literature sources indicate the fact of cumulative change, where at the age up to 15 years in 1.5% of children if there is at least one unprovoked seizure, then in the future in 1% of these same children epileptic seizures continue to recur in adulthood.
Keywords: : Clinical And Neurophysiologic Verification; Age Difference Of Epilepsy; Children And Adolescents